A preparation method of nano calcium carbonate crystal shape control agent and crystal shape control agent
Through magnetic stirring, ultrasonic dispersion and vacuum drying, combined with graphene proportional parameter control, the problem of difficult control of nano-scale calcium carbonate particle size and morphology is solved, and the stability and performance of nano-calcium carbonate crystal particle size is achieved. optimization.
Patent Information
- Application Number
- CN202211701610.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-28
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-12-28
AI Technical Summary
The prior art is difficult to effectively control the particle size and morphology of nano-scale calcium carbonate, resulting in poor particle size consistency of the prepared nano-scale calcium carbonate crystal form, and it is impossible to prepare nano-scale calcium carbonate with uniform particle size.
A nano-calcium carbonate crystal form control agent preparation method is adopted, through magnetic stirring, ultrasonic dispersion, vacuum drying and grinding, combined with the proportional parameter control of one-dimensional, two-dimensional and three-dimensional graphene, mixed graphene is formed to prepare nano-calcium carbonate. , ensure the stability of particle size distribution.
The stable control of the crystal particle size of nano-scale calcium carbonate is achieved, and nano-calcium carbonate products with excellent performance are obtained, with uniform particle size distribution and good dispersion.
Smart Images

Figure CN116409807B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano calcium carbonate materials, and particularly relates to a preparation method of a nano calcium carbonate crystal shape control agent and the crystal shape control agent. Background Art
[0002] Nano-scale calcium carbonate is less than 100 nanometers in size. It is a new type of solid material with excellent reinforcement. Its particle size is small, and it has macroscopic quantum tunneling effect, micro-volume effect and surface effect. It is widely used in rubber, plastic, papermaking, ink, coating and other fields. The particle morphology, crystal structure and particle size of nano-calcium carbonate vary. According to the particle morphology, it can be divided into special morphologies such as irregular type, square type, spherical type, chain type and needle type, and its performance is different. Spherical nano-calcium carbonate has a simple structure, small stacking volume, low oil absorption value, excellent smoothness and fluidity, high hiding power and strong absorption of ink. It is mainly used in the papermaking industry and the production of lubricating oils. Cubic nano-calcium carbonate has a regular morphology and is mainly used in papermaking, which greatly improves the light-shielding and whiteness of paper and makes the paper smoother. It can also be used in the production of plastics to improve the strength of products. Needle-shaped nano-calcium carbonate has a complete crystal structure, good reinforcement and toughening effect, and can improve the strength and elongation of materials. Chain-shaped calcium carbonate is an excellent reinforcing filler. When it participates in the preparation process of rubber, the chain will be broken, thus forming a highly active point, which will then bond with the rubber chain to enhance the reinforcement effect. Flake nano calcium carbonate has a strong coating function, good covering performance, and certain printability, so it is widely used in the papermaking industry.
[0003] However, the particle size and morphology of nano-calcium carbonate prepared by the current method are difficult to control. For example, when preparing spindle-shaped, cubic or rod-shaped nano-calcium carbonate, the morphology is mostly controlled by stirring and drying time, which results in poor dispersion effect. During subsequent grinding, the particle size consistency of the prepared nano-calcium carbonate crystals is very likely to be poor, and nano-calcium carbonate with uniform particle size cannot be prepared. Summary of the invention
[0004] In order to solve the above problems existing in the prior art, the present invention provides a catalyst preparation method and catalyst for improving the amount of hydrogen released by hydrolysis of nano-aluminum. The technical problem to be solved by the present invention is achieved by the following technical solutions:
[0005] A method for preparing a nano calcium carbonate crystal shape control agent, comprising:
[0006] Step 1, placing the first compound in a magnetic stirrer and adding deionized water, heating in a water bath and stirring for 0.5-2h, when the temperature reaches 60-70°C, adding the second compound and stirring to obtain a mixed solution;
[0007] Step 2, preparing hybrid graphene;
[0008] Step 3, adding the mixed graphene to a dispersant for ultrasonic dispersion, and adding the dispersed mixed graphene to a vacuum drying oven for drying at 40-100° C. to obtain dried mixed graphene;
[0009] Step 4, adding the dried mixed graphene into the mixed solution, stirring and drying to obtain solid particles;
[0010] Step 5, grinding the solid particles in a mortar to obtain a crystal shape controlling agent.
[0011] In one embodiment, the steps of preparing the hybrid graphene include:
[0012] A, adding the same mass of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene into a dispersant, performing ultrasonic dispersion, and vacuum drying to obtain a dry one-dimensional graphene sample, a dry two-dimensional graphene sample, and a dry three-dimensional graphene sample;
[0013] B, prepare three mixed solution samples according to the method of step 1;
[0014] C, respectively adding a dried one-dimensional graphene sample, a dried two-dimensional graphene sample, and a dried three-dimensional graphene sample to the mixed solution sample for stirring, drying, and grinding to obtain a first crystal shape control agent sample, a second crystal shape control agent sample, and a third crystal shape control agent sample;
[0015] D, take three portions of CaO and add deionized water respectively to obtain three portions of Ca(OH)2 suspension samples;
[0016] E. Add the first crystal shape control agent sample, the second crystal shape control agent sample, and the third crystal shape control agent sample to three Ca(OH)2 suspension samples respectively, and introduce CO2 to fully carbonize the calcium hydroxide;
[0017] F, measure the pH value of three samples of Ca(OH)2 suspension, and stop introducing CO2 until the pH value reaches 7-8;
[0018] G. After aging for 12-24 hours, the reaction solution is filtered and the product sample is dried, and the product sample is ground and sieved to obtain a first nano-calcium carbonate sample, a second nano-calcium carbonate sample, and a third nano-calcium carbonate sample respectively;
[0019] H, calculate the proportion of particles smaller than the preset size in the first nano-calcium carbonate sample as the first percentage t1, the proportion of particles larger than the preset size in the second nano-calcium carbonate sample as the second percentage t2, and the proportion of particles larger than the preset size in the third nano-calcium carbonate sample as the second percentage t3;
[0020] I, preparing a mixed graphene according to the first percentage t1, the second percentage t2, and the second percentage t3, wherein the ratio of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene in the mixed graphene is:
[0021]
[0022] In a specific embodiment, the ratio of the first compound to deionized water is 1:1-1:5.
[0023] In a specific embodiment, the first compound is an organic compound, and the second compound is a rare earth compound or a metal compound.
[0024] In a specific embodiment, the earth compound includes one or more of chlorides, nitrates, and sulfates of rare earth.
[0025] In a specific embodiment, the metal compound includes one or more of metal chlorides, nitrates, and sulfates.
[0026] In a specific embodiment, the dispersant is ethanol.
[0027] The present invention also provides a nano-calcium carbonate crystal shape controller, which is prepared by the above-mentioned nano-calcium carbonate crystal shape controller preparation method.
[0028] Beneficial effects of the present invention:
[0029] The method for preparing the nano calcium carbonate crystal shape controller of the present invention determines the ratio parameters of the three by analyzing the mixing of one-dimensional, two-dimensional and three-dimensional graphene with reactants after being dispersed in a dispersant, and then mixes the three according to the parameters to form mixed graphene, which is then dispersed, so that the one-dimensional graphene, two-dimensional graphene and three-dimensional graphene can all be effectively utilized, thereby making the crystal particle size of the prepared nano-scale calcium carbonate stably controlled and being able to obtain a product with excellent performance.
[0030] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic flow chart of a method for preparing a nano-calcium carbonate crystal shape control agent provided by an embodiment of the present invention;
[0032] Figure 2 is a SEM image of spindle-shaped nano-calcium carbonate provided by an embodiment of the present invention;
[0033] Figure 3 is a SEM image of cubic nano-calcium carbonate provided by an embodiment of the present invention;
[0034] Figure 4It is a SEM picture of the rod-shaped nano calcium carbonate provided in the embodiment of the present invention. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below with reference to specific embodiments, but the embodiments of the present invention are not limited thereto.
[0036] Embodiment 1
[0037] See also Figure 1 , Figure 1 The present invention provides a method for preparing a nano-calcium carbonate crystal shape control agent, which comprises:
[0038] Step 1, placing the first compound in a magnetic stirrer and adding deionized water, heating in a water bath and stirring for 0.5-2h, when the temperature reaches 60-70°C, adding the second compound and stirring to obtain a mixed solution;
[0039] Step 2, preparing hybrid graphene;
[0040] Step 3, adding the mixed graphene to a dispersant for ultrasonic dispersion, and adding the dispersed mixed graphene to a vacuum drying oven for drying at 40-100° C. to obtain dried mixed graphene;
[0041] Step 4, adding the dried mixed graphene into the mixed solution, stirring and drying to obtain solid particles;
[0042] Step 5, grinding the solid particles in a mortar to obtain a crystal shape controlling agent.
[0043] In one embodiment, the steps of preparing the hybrid graphene include:
[0044] A, adding the same mass of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene into a dispersant, performing ultrasonic dispersion, and vacuum drying to obtain a dry one-dimensional graphene sample, a dry two-dimensional graphene sample, and a dry three-dimensional graphene sample;
[0045] B. Prepare a mixed solution sample according to the method of step 1, and divide the mixed solution sample into three parts;
[0046] C, respectively adding a dried one-dimensional graphene sample, a dried two-dimensional graphene sample, and a dried three-dimensional graphene sample to the mixed solution sample for stirring, drying, and grinding to obtain a first crystal shape control agent sample, a second crystal shape control agent sample, and a third crystal shape control agent sample;
[0047] D, take three portions of CaO and add deionized water respectively to obtain three portions of Ca(OH)2 suspension samples;
[0048] E. Add the first crystal shape control agent sample, the second crystal shape control agent sample, and the third crystal shape control agent sample to three Ca(OH)2 suspension samples respectively, and introduce CO2 to fully carbonize the calcium hydroxide;
[0049] F, measure the pH value of three samples of Ca(OH)2 suspension, and stop introducing CO2 until the pH value reaches 7-8;
[0050] G. After aging for 12-24 hours, the reaction solution is filtered and the product sample is dried, and the product sample is ground and sieved to obtain a first nano-calcium carbonate sample, a second nano-calcium carbonate sample, and a third nano-calcium carbonate sample respectively;
[0051] H, calculate the proportion of particles smaller than the preset size in the first nano-calcium carbonate sample as the first percentage t1, the proportion of particles larger than the preset size in the second nano-calcium carbonate sample as the second percentage t2, and the proportion of particles larger than the preset size in the third nano-calcium carbonate sample as the second percentage t3;
[0052] I, preparing a mixed graphene according to the first percentage t1, the second percentage t2, and the second percentage t3, wherein the ratio of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene in the mixed graphene is:
[0053]
[0054] In a specific embodiment, the ratio of the first compound to deionized water is 1:1-1:5.
[0055] In a specific embodiment, the first compound is an organic compound, and the second compound is a rare earth compound or a metal compound.
[0056] In a specific embodiment, the earth compound includes one or more of chlorides, nitrates, and sulfates of rare earth.
[0057] In a specific embodiment, the metal compound includes one or more of metal chlorides, nitrates, and sulfates.
[0058] In a specific embodiment, the dispersant is ethanol.
[0059] This embodiment also provides a nano-calcium carbonate crystal shape control agent, which is prepared by the above-mentioned nano-calcium carbonate crystal shape control agent preparation method.
[0060] The method for preparing the nano-calcium carbonate crystal shape controller of the present embodiment determines the ratio parameters of the three by analyzing the mixing of one-dimensional, two-dimensional and three-dimensional graphene with reactants after dispersion in a dispersant, and then mixes the three according to the parameters to form mixed graphene, which is then dispersed, so that the one-dimensional graphene, two-dimensional graphene and three-dimensional graphene can all be effectively utilized, thereby making the crystal shape control of the prepared spindle-shaped nano-scale calcium carbonate stable, and being able to obtain a product with excellent performance.
[0061] Embodiment 2
[0062] Step 1, placing 50 g of sodium citrate in a magnetic stirrer and adding deionized water, heating in a water bath and stirring for 1 h, when the temperature reaches 60° C., adding 10 g of lanthanum nitrate and stirring for 1 h to obtain a mixed solution;
[0063] Step 2, preparing hybrid graphene.
[0064] A, adding 0.01 g of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene into a dispersant, performing ultrasonic dispersion, and vacuum drying to obtain a dry one-dimensional graphene sample, a dry two-dimensional graphene sample, and a dry three-dimensional graphene sample;
[0065] B, prepare three mixed solution samples of 1 g according to the method of step 1;
[0066] C, respectively adding a dried one-dimensional graphene sample, a dried two-dimensional graphene sample, and a dried three-dimensional graphene sample to the mixed solution sample for stirring, drying, and grinding to obtain a first crystal shape control agent sample, a second crystal shape control agent sample, and a third crystal shape control agent sample;
[0067] D, take three portions of 5g CaO and add 100mL of deionized water respectively, heat in a 60℃ water bath and stir for 1h, let stand and age for 12h, and obtain three portions of Ca(OH)2 suspension samples;
[0068] E. Add the first crystal shape control agent sample, the second crystal shape control agent sample, and the third crystal shape control agent sample to three Ca(OH)2 suspension samples respectively, and introduce CO2 to fully carbonize the calcium hydroxide;
[0069] F, measure the pH value of three samples of Ca(OH)2 suspension, and stop introducing CO2 until the pH value reaches 7;
[0070] G, after aging for 12 hours, the reaction solution was filtered and the product sample was dried in a drying oven, wherein the drying was carried out in the drying oven for 2 hours at a drying temperature of 80° C. The product sample was ground and sieved to obtain a first nano-calcium carbonate sample, a second nano-calcium carbonate sample, and a third nano-calcium carbonate sample respectively;
[0071] H, calculate the proportion of particles with a diameter less than 70 nm in the first nano-calcium carbonate sample as a first percentage t1, the proportion of particles with a diameter greater than 70 nm in the second nano-calcium carbonate sample as a second percentage t2, and the proportion of particles with a diameter greater than 70 nm in the third nano-calcium carbonate sample as a second percentage t3;
[0072] I, preparing a mixed graphene according to the first percentage t1, the second percentage t2, and the second percentage t3, wherein the ratio of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene in the mixed graphene is:
[0073] The ratio measured in this embodiment is 0.8:0.15:0.05.
[0074] Step 3, adding the mixed graphene to a dispersant in a ratio of 0.8:0.15:0.05 and performing ultrasonic dispersion for 0.5 h, adding the dispersed mixed graphene to a vacuum drying oven and drying it at 60° C. for 2 h to obtain dried mixed graphene;
[0075] Step 4, adding the dried mixed graphene to the mixed solution, stirring for 1 hour and drying at room temperature for 72 hours to obtain solid particles;
[0076] Step 5, grinding the solid particles in a mortar to obtain a crystal shape control agent. Figure 2 The SEM image of spindle-shaped nano calcium carbonate is shown. The nano calcium carbonate prepared in this embodiment is spindle-shaped, has uniform particle size distribution, large aspect ratio and good dispersibility.
[0077] Embodiment 3
[0078] Step 1, placing 50 g of sodium citrate in a magnetic stirrer and adding deionized water, heating in a water bath and stirring for 1 h, when the temperature reaches 60° C., adding 10 g of lanthanum nitrate and stirring for 1 h to obtain a mixed solution;
[0079] Step 2, preparing hybrid graphene.
[0080] A, adding 0.01 g of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene into a dispersant, performing ultrasonic dispersion, and vacuum drying to obtain a dry one-dimensional graphene sample, a dry two-dimensional graphene sample, and a dry three-dimensional graphene sample;
[0081] B, prepare three mixed solution samples of 1 g according to the method of step 1;
[0082] C, respectively adding a dried one-dimensional graphene sample, a dried two-dimensional graphene sample, and a dried three-dimensional graphene sample to the mixed solution sample for stirring, drying, and grinding to obtain a first crystal shape control agent sample, a second crystal shape control agent sample, and a third crystal shape control agent sample;
[0083] D, take three portions of 10g CaO and add 100mL of deionized water respectively, heat in a 60℃ water bath and stir for 2h, let stand and age for 24h, and obtain three Ca(OH)2 suspension samples;
[0084] E. Add the first crystal shape control agent sample, the second crystal shape control agent sample, and the third crystal shape control agent sample to three Ca(OH)2 suspension samples respectively, and introduce CO2 to fully carbonize the calcium hydroxide;
[0085] F, measure the pH value of three samples of Ca(OH)2 suspension, and stop introducing CO2 until the pH value reaches 8;
[0086] G. After aging for 12 hours, the reaction solution was filtered and the product sample was dried in a drying oven, wherein the drying was performed in the drying oven for 2 hours at a drying temperature of 100° C. The product sample was ground and sieved to obtain a first nano-calcium carbonate sample, a second nano-calcium carbonate sample, and a third nano-calcium carbonate sample respectively;
[0087] H, calculate the proportion of particles with a diameter less than 60 nm in the first nano-calcium carbonate sample as a first percentage t1, the proportion of particles with a diameter greater than 60 nm in the second nano-calcium carbonate sample as a second percentage t2, and the proportion of particles with a diameter greater than 60 nm in the third nano-calcium carbonate sample as a second percentage t3;
[0088] I, preparing a mixed graphene according to the first percentage t1, the second percentage t2, and the second percentage t3, wherein the ratio of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene in the mixed graphene is:
[0089] The ratio measured in this implementation is 0.76:0.16:0.08.
[0090] Step 3, adding the mixed graphene to the dispersant in a ratio of 0.76:0.16:0.08 for ultrasonic dispersion for 0.5 h, adding the dispersed mixed graphene to a vacuum drying oven for drying at 60° C. for 2 h to obtain dried mixed graphene;
[0091] Step 4, adding the dried mixed graphene to the mixed solution, stirring for 1 hour and drying at room temperature for 72 hours to obtain solid particles;
[0092] Step 5, grinding the solid particles in a mortar to obtain a crystal shape control agent. Figure 3 The SEM image of cubic nano-calcium carbonate is shown. The nano-calcium carbonate prepared in this embodiment is cubic nano-calcium carbonate with uniform particle size distribution and good dispersibility.
[0093] Embodiment 4
[0094] Step 1, placing 50 g of sodium citrate in a magnetic stirrer and adding deionized water, heating in a water bath and stirring for 1 h, when the temperature reaches 60° C., adding 10 g of lanthanum nitrate and stirring for 1 h to obtain a mixed solution;
[0095] Step 2, preparing hybrid graphene.
[0096] A, adding 0.01 g of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene into a dispersant, performing ultrasonic dispersion, and vacuum drying to obtain a dry one-dimensional graphene sample, a dry two-dimensional graphene sample, and a dry three-dimensional graphene sample;
[0097] B, prepare three mixed solution samples of 1 g according to the method of step 1;
[0098] C, respectively adding a dried one-dimensional graphene sample, a dried two-dimensional graphene sample, and a dried three-dimensional graphene sample to the mixed solution sample for stirring, drying, and grinding to obtain a first crystal shape control agent sample, a second crystal shape control agent sample, and a third crystal shape control agent sample;
[0099] D, take three portions of 12g CaO and add 60mL of deionized water respectively, heat in a water bath at 80℃ and stir for 2h, let stand and age for 24h, and obtain three Ca(OH)2 suspension samples;
[0100] E. Add the first crystal shape control agent sample, the second crystal shape control agent sample, and the third crystal shape control agent sample to three Ca(OH)2 suspension samples respectively, and introduce CO2 to fully carbonize the calcium hydroxide;
[0101] F, measure the pH value of three samples of Ca(OH)2 suspension, and stop introducing CO2 until the pH value reaches 8;
[0102] G. After aging for 12 hours, the reaction solution was filtered and the product sample was dried in a drying oven, wherein the drying was performed in the drying oven for 2 hours at a drying temperature of 100° C. The product sample was ground and sieved to obtain a first nano-calcium carbonate sample, a second nano-calcium carbonate sample, and a third nano-calcium carbonate sample respectively;
[0103] H, calculate the proportion of particles with a diameter less than 40 nm in the first nano-calcium carbonate sample as a first percentage t1, the proportion of particles with a diameter greater than 40 nm in the second nano-calcium carbonate sample as a second percentage t2, and the proportion of particles with a diameter greater than 40 nm in the third nano-calcium carbonate sample as a second percentage t3;
[0104] I, preparing a mixed graphene according to the first percentage t1, the second percentage t2, and the second percentage t3, wherein the ratio of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene in the mixed graphene is:
[0105] The ratio measured in this embodiment is 0.62:0.22:0.16.
[0106] Step 3, adding the mixed graphene to the dispersant in a ratio of 0.62:0.22:0.16 for ultrasonic dispersion for 0.5 h, adding the dispersed mixed graphene to a vacuum drying oven for drying at 60° C. for 2 h to obtain dried mixed graphene;
[0107] Step 4, adding the dried mixed graphene to the mixed solution, stirring for 1 hour and drying at room temperature for 72 hours to obtain solid particles;
[0108] Step 5, grinding the solid particles in a mortar to obtain a crystal shape control agent. Figure 3 The SEM image of the rod-shaped nano calcium carbonate is shown. The nano calcium carbonate prepared in this embodiment is rod-shaped nano calcium carbonate with uniform particle size distribution and good dispersibility.
[0109] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0110] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.
[0111] Although the present application is described herein in conjunction with various embodiments, in the process of implementing the claimed application, those skilled in the art may understand and implement other variations of the disclosed embodiments by viewing the drawings, the disclosure, and the appended claims. In the claims, the word "comprising" does not exclude other components or steps, and "one" or "an" does not exclude multiple situations. A single processor or other unit may implement several functions listed in a claim. Certain measures are recorded in different dependent claims, but this does not mean that these measures cannot be combined to produce good results.
[0112] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.
Claims
1. A method for preparing a nano calcium carbonate crystal shape control agent, It is characterized in that include: Step 1, placing a first compound in a magnetic stirrer and adding deionized water, heating in a water bath and stirring for 0.5-2h, and when the temperature reaches 60-70°C, adding a second compound and stirring to obtain a mixed solution, wherein the first compound is sodium citrate and the second compound is lanthanum nitrate; Step 2, preparing hybrid graphene; Step 3, adding the mixed graphene to a dispersant for ultrasonic dispersion, and adding the dispersed mixed graphene to a vacuum drying oven for drying at 40-100° C. to obtain dried mixed graphene; Step 4, adding the dried mixed graphene into the mixed solution, stirring and drying to obtain solid particles; Step 5, grinding the solid particles in a mortar to obtain a crystal shape control agent; The steps of preparing hybrid graphene include: A, adding the same mass of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene into a dispersant, performing ultrasonic dispersion, and vacuum drying to obtain a dry one-dimensional graphene sample, a dry two-dimensional graphene sample, and a dry three-dimensional graphene sample; B, prepare three mixed solution samples according to the method of step 1; C, respectively adding a dried one-dimensional graphene sample, a dried two-dimensional graphene sample, and a dried three-dimensional graphene sample to the mixed solution sample for stirring, drying, and grinding to obtain a first crystal shape control agent sample, a second crystal shape control agent sample, and a third crystal shape control agent sample; D, take three parts of CaO and add deionized water respectively to obtain three parts of Ca(OH) 2 Suspension samples; E, in three parts Ca(OH) 2 The first crystal shape control agent sample, the second crystal shape control agent sample, and the third crystal shape control agent sample were added to the suspension sample and CO was introduced. 2 To fully carbonize calcium hydroxide; F, three determinations of Ca(OH) 2 The pH value of the suspension sample was adjusted until the pH value reached 7-8, and the CO was stopped. 2 ; G. After aging for 12-24 hours, the reaction solution is filtered and the product sample is dried, and the product sample is ground and sieved to obtain a first nano-calcium carbonate sample, a second nano-calcium carbonate sample, and a third nano-calcium carbonate sample respectively; H, calculate the proportion of particles smaller than a preset size in the first nano-calcium carbonate sample as a first percentage t1, the proportion of particles larger than a preset size in the second nano-calcium carbonate sample as a second percentage t2, and the proportion of particles larger than a preset size in the third nano-calcium carbonate sample as a third percentage t3; I, preparing a mixed graphene according to the first percentage t1, the second percentage t2, and the third percentage t3, wherein the ratio of one-dimensional graphene, two-dimensional graphene, and three-dimensional graphene in the mixed graphene is:
2. The method for preparing a nano calcium carbonate crystal shape control agent according to claim 1, It is characterized in that The ratio of the first compound to deionized water is 1:1-1:
5.
3. The method for preparing a nano calcium carbonate crystal shape control agent according to claim 1, It is characterized in that The dispersant is ethanol.
4. A nano calcium carbonate crystal shape control agent, It is characterized in that The nano calcium carbonate crystal shape control agent is prepared by the preparation method of the nano calcium carbonate crystal shape control agent according to any one of claims 1 to 3.
Citation Information
Patent Citations
Preparation method of flake-stacked cube-shaped micron-sized calcium carbonate
CN104445334A
Method for regulating and controlling preparation of nano calcium carbonate by using crystal form control agent
CN111268712A
